Model Pemahaman Front Pembela Islam (FPI) Terhadap Al-Qur’an Dan Hadis - Abdul Hakim Wahid (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2018)
The Islamic Defenders Front (FPI) is very famous for the amar ma'ruf and nahi mungkar movement, and launched the national anti-immoral movement. However their movement always seems to use violence, so there is a presumption that FPI's religious pattern shows the influence of petro Islam that rigidly and textually-dominated with a harsh understanding to the practice of violation on religious values. With the semantic approach to the Habib Riziq’s book entitled Dialog FPI-Amar Ma'ruf Nahi Munkar, this paper prove that the FPI's interpretation to the Qur'an and hadiths which is the reference of their every action, has used a contextual approach, but seems that their understanding is less comprehensive.